More than crave you eaudiobook - Black, Shayla (Reed Family Reckoning, 2018)
I'm Evan Cook—billionaire tech entrepreneur and widower. Professionally, I've got it all. But since my wife died, my personal life has fallen apart. Remarrying seems like the obvious answer, so I place an ad. I'm not asking for much. The ideal woman only needs to be smart, organized, pretty, and helpful—both in and out of bed—without expecting romance. I never thought to look right in front of me . . . but it turns out that Nia Wright, my sexy, sassy assistant, just might be the perfect candidate. After an unexpectedly hot night together, I'm ready to stop interviewing strangers and simply marry her. On paper, she ticks every box on my list. Best of all, she's far too sensible to fall for me. I didn't see the flaw in my logic until it was too late. I never thought I'd lose my heart for the first time. And I definitely never imagined Nia could consume me. But she's harboring a secret that could tear us apart. Can I prove I more than crave her before it's too late? Contains mature themes.